PUSAT PERAWATAN KESEHATAN LANSIA DENGAN PENDEKATAN ARSITEKTUR BIOFILIK DI KABUPATEN HULU SUNGAI TENGAH - Rihmayana, Rihmayana; Mochamad, Bani Noor (UNIVERSITAS LAMBUNG MANGKURAT, 2022)
Elderly or can be called elderly is the last stage of the life process experienced by humans,which results in a decrease in the ability to live. Judging from the increasing population growth and theproblems faced by the elderly such as neglected elderly, it is necessary to have alternative means toprovide physical and mental health facilities. Then the Elderly Health Care Center becomes atechnical implementation unit that provides social services that support the process of improvinghealth and social welfare. Biophilic architecture is the basis for this design, which is an approach thatutilizes natural elements as an aspect that can have a positive impact on physical and psychologicalconditions in the elderly.